2011
DOI: 10.1080/08989621.2011.575034
|View full text |Cite
|
Sign up to set email alerts
|

The Microphysics of Accountability

Abstract: How is it possible to deploy the law to create and perform accountability? To answer this question, I address the argumentative function of the law in order to legitimize genetic medicine. Using interview data, I will in particular elaborate on how medical experts strive to convince interviewing social scientists that their own professional action is above all ethical reproach. For this purpose, medical experts capitalize on the law in specific ways. It is the aim of this article to expound exactly how this ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…For an assessment in terms of the conceptual use of GR, we looked for conclusive definitions of GR in the studies and tracked quotations and references that might expose a theoretical discussion of GR. While we only found 21 studies offering a conclusive definition of GR (Burgess and d' Agincourt-Canning, 2001;d' Agincourt-Canning, 2001Downing, 2005;Hallowell et al, 2006;Arribas-Ayllon et al, 2008a,b, 2011Bickerstaff et al, 2008;Etchegary and Fowler, 2008;Etchegary et al, 2009Etchegary et al, , 2015Raz and Schicktanz, 2009;Dancyger et al, 2010;Hines et al, 2010;Clarke et al, 2011;Weiner, 2011;Donnelly et al, 2013;Boardman, 2014b;D' Audiffret Van Haecke and de Montgolfier, 2015;Ross, 2015), all but 17 of the included studies made reference to non-empirical literature, such as philosophical or bioethical papers referring to or using GR (cf. Data Sheet 1).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…For an assessment in terms of the conceptual use of GR, we looked for conclusive definitions of GR in the studies and tracked quotations and references that might expose a theoretical discussion of GR. While we only found 21 studies offering a conclusive definition of GR (Burgess and d' Agincourt-Canning, 2001;d' Agincourt-Canning, 2001Downing, 2005;Hallowell et al, 2006;Arribas-Ayllon et al, 2008a,b, 2011Bickerstaff et al, 2008;Etchegary and Fowler, 2008;Etchegary et al, 2009Etchegary et al, , 2015Raz and Schicktanz, 2009;Dancyger et al, 2010;Hines et al, 2010;Clarke et al, 2011;Weiner, 2011;Donnelly et al, 2013;Boardman, 2014b;D' Audiffret Van Haecke and de Montgolfier, 2015;Ross, 2015), all but 17 of the included studies made reference to non-empirical literature, such as philosophical or bioethical papers referring to or using GR (cf. Data Sheet 1).…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…For example, in the same study, genetic counselors "recognize that the law gives them something to fall back on in 'those rare cases' where patients refuse to warn at-risk relatives (I1), to 'counter refusals when the reasons are as much to do with family feuds, geographic separation, or fear of genetics and the allied denial as anything else' (I7)" [D' Audiffret Van Haecke and de Montgolfier (2015), p. 6]. Other professionals "took the stance that there was no real need to legislate since informing patients of risks to relatives is part of professional duty, and developing disclosure support is part of professional practice ( Non-performance of professional GR was also an important issue in an Austrian study, which found that reference to legal regulations or to the medical code of conduct served as a rhetorical strategy for genetic professionals to repudiate GR in ethical dilemmas (Wieser, 2011). Hinting at the fact that genetic professionals, who are the experts for the issues under legal regulation, contributed to existing legal regulation and hence were at least partly responsible for it, the study revealed their denial of responsibility as morally flawed:…”
Section: Professional Gr (C)mentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the establishment of legal restrictions and prohibitions relieves the professions of much of the engagement with ethical and social questions. The argument may seem counterintuitive at first glance, but in his contribution to this issue, Wieser shows how it does shape a specific pattern of accountability (Wieser, 2011).…”
Section: Genomics Truth and Accountabilitymentioning
confidence: 94%